2015
DOI: 10.3989/scimar.04049.12a
|View full text |Cite
|
Sign up to set email alerts
|

Effects of light quality on reproduction, growth and pigment content of <em>Gracilaria birdiae</em> (Rhodophyta: Gracilariales)

Abstract: Summary: Gracilaria species are the main source of agar worldwide. Since laboratory cultivation is an important means of sustaining such production, this study aimed to assess the influence of two fundamental strategies of physiological algae adjustment, photoacclimation and photomorphogenesis, on G. birdiae physiology. Specifically, the effects of different spectral light qualities on reproduction, growth, and pigment content in two distinct photoperiods (8 and 14 hours) were examined. Tetrasporophytes and ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 47 publications
(54 reference statements)
0
7
0
1
Order By: Relevance
“…Moreover, Tsekos et al [40], Franklin et al [41], and Barufi et al [5] also found that B light could, respectively, increase the PE and PC concentration of Pyropia leucosticta , Chondrus crispus, and Gracilaria birdiae . B and G light help promote the nitrogen accumulation, and these wavelengths could induce soluble protein and phycobiliproteins formation [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Tsekos et al [40], Franklin et al [41], and Barufi et al [5] also found that B light could, respectively, increase the PE and PC concentration of Pyropia leucosticta , Chondrus crispus, and Gracilaria birdiae . B and G light help promote the nitrogen accumulation, and these wavelengths could induce soluble protein and phycobiliproteins formation [6].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the bright red and blue light can increase the ratio of fucoxanthin to Chl a and Chl c : a ratio in Laminaria hyperborea [4]. Furthermore, Barufi et al [5] reported that growth rates were higher in Gracilaria birdiae exposed to white light and red light could be utilized as a reproductive inductor to produce tetraspores. Green light could also be beneficial for algal growth of Halymenia floresia .…”
Section: Introductionmentioning
confidence: 99%
“…Light-emitting diodes (LEDs) produce monochromatic light in an energy-efficient way, suggesting their potential to provide supplementary light for seaweed growth (Bourget, 2008;Kim et al, 2015). By filtering fluorescent light with band-pass filters, monochromatic lights have been produced to promote seaweed growth, and their influence has been tested on several seaweed species (Figueroa & Niell, 1990;Figueroa et al, 1995;Korbee, Figueroa & Aguilera, 2005;Kim et al, 2015;Bonomi Barufi, Figueroa & Plastino, 2015). In general, compared to fluorescent light culturing, the seaweed growth rate could be increased by 10-60% under suitable LED light conditions (Schulze et al, 2016;Kim, Choi & Lee, 2019;Gong, Liu & Zou, 2020;Öztaşkent & Ak, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In general, compared to fluorescent light culturing, the seaweed growth rate could be increased by 10-60% under suitable LED light conditions (Schulze et al, 2016;Kim, Choi & Lee, 2019;Gong, Liu & Zou, 2020;Öztaşkent & Ak, 2020). However, although LED light has been proposed as a light source for Gracilaria cultivation (Kim et al, 2015;Bonomi Barufi, Figueroa & Plastino, 2015), its influence on a broader variety of seaweed species and their biosynthesis remains poorly understood. Besides, different wavelengths of lights vary in their ability to penetrate water.…”
Section: Introductionmentioning
confidence: 99%
“…Light characteristics have a profound influence on microalgae metabolism and development. Barufi, Figueroa & Plastino (2015) reported that growth rates were higher in Gracilaria birdiae exposed to white light, and Sharmila et al (2018) concluded that the yellow color light could be used for the more lipid production, whereas blue light for biomass and pigments.…”
Section: Introductionmentioning
confidence: 99%